Analysis of Fourier Series in Acoustic - Syahirah Nadhrah binti Roslan,; Muhammad Basri, Cik Sri Mazzura (Enhanced Knowledge in Sciences and Technology, 2022)
There is a relationship between sounds and the Fourier series. Some researchers found that the Fourier series is one of the applications in music that calculates the frequency by using the amplitude of the wave. Nowadays, most of the sounds that have been exposed to the kids are more random and do not have any range that the guardian put on a limit that can damage their hearing. Therefore, the aims of the research are to study the method of Fourier series in acoustics and develop simulation the using MATLAB. The Fourier series and partial differential equation has been used because the variable and formula are suitable for sound with periodic function. Then, the wave motion from the sound is analysed using the platform of the graph. Three data have been used in this research to compare and make a conclusion from the difference in the pattern of the graphs shown. The analysis from the research shows that when the frequency increase, the number of waves also increases. Therefore, we can conclude that the higher frequency can affect the kids’ hearing because the motion of waves that the kids receive is high.